Effects of varieties and planting geometries on growth and yield of rain-fed rice in Dailekh, Nepal - Pariyar, Kiran; Sapkota, Pradip; Panta, Salina; Sharma, Sashiram; Karki, Tika Bahadur (Journal of Agriculture and Natural Resources, 2019)
A study was conducted at outreach sites of Horticulture Research Station, Dailekh with the objective of understanding effects of variety selection and spacing under rain-fed condition, during two rainy seasons of 2016 and 2017. Experiment was conducted in two factorial Randomized Complete Block Design where the research sites were replication itself. First factor was variety, including Khumal-10 and farmer’s variety. The second factor was spacings at (20x20) cm, (20x15) cm, (15x15) cm, and farmer’s practice. Effect of Khumal-10 was significantly superior in each of the parameters studied, except days to heading and maturity. Khumal-10, alone contributed 21.6% more yield compared to the farmer’s variety and also had the tallest plant (127.5 cm) and longest panicle (23.4 cm). Similarly, transplantation at spacing of (15x15) cm was significantly outstanding with 28.6% more grain yield, unlike in transplantation with farmer’s practice. Furthermore, integrated management of rice with Khumal-10 transplanted at spacing of (15x15) cm is recommended for Dailekh condition, since it resulted significantly promising grain yield of 5.5 t/ha, which is 71.9% more in comparison to grain yield from farmer’s variety transplanted in farmers´ practice.  Also, the economic benefit was highest with 75.8% more B:C ratio in case of improved variety Khumal-10 transplanted at (15x15) cm spacing.